2014
DOI: 10.1002/ehf.212003
|View full text |Cite
|
Sign up to set email alerts
|

The late sodium current in heart failure: pathophysiology and clinical relevance

Abstract: Large and growing body of data suggest that an increased late sodium current (I Na,late ) can have a significant pathophysiological role in heart failure and other heart diseases. The first goal of this article is to describe how I Na,late functions under physiological circumstances. The second goal is to show the wide range of cellular mechanisms that can increase I Na,late in cardiac disease, and also to describe how the up-regulated I Na,late contributes to the pathophysiology of heart failure. The final se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 178 publications
2
6
0
Order By: Relevance
“…A review from Harvath and Bers found that the increased late sodium current also contributed to Ca 2+ modulation to cause heart failure, which was associated with increased ROS. 29 Our data showed that RAN treatment abrogated CKD-affected Ca 2+ transient, decay time and AP, which suggests that a deterioration of Na + regulation also modulated intracellular Ca 2+ handling in CKD.…”
Section: Ca 2+ Handling In Cardiomyocytes Of Ckd Micesupporting
confidence: 54%
“…A review from Harvath and Bers found that the increased late sodium current also contributed to Ca 2+ modulation to cause heart failure, which was associated with increased ROS. 29 Our data showed that RAN treatment abrogated CKD-affected Ca 2+ transient, decay time and AP, which suggests that a deterioration of Na + regulation also modulated intracellular Ca 2+ handling in CKD.…”
Section: Ca 2+ Handling In Cardiomyocytes Of Ckd Micesupporting
confidence: 54%
“…Detrimental alterations in sodium and calcium homeostasis contribute to ischemia-reperfusion (IR) injury and the development of heart failure, 19 representing an attractive therapeutic target. 20 A major pathway involved is the metabolic imbalance-mediated induction of the late/persistent component of the cardiac voltage-gated sodium channel (late- I Na ) 19 , 21 23 and increased NHE1 (sodium-hydrogen exchanger isoform 1) activity. 24 The excessive sodium influx leads to the induction of reverse-mode NCX1.1 (sodium/calcium exchanger isoform 1.1) activity and consequent calcium loading within cardiomyocytes.…”
mentioning
confidence: 99%
“… 32 35 Because late- I Na is induced only in disease states, it is considered to be a promising target for the treatment of heart failure and arrhythmias. 23 , 29 , 36 38 Moreover, congenital LQT3 mutations in the human SCN5A gene encoding the major cardiac sodium channel isoform Nav1.5 lead to induction of late- I Na , which increases sodium entry and action potential duration that precipitates altered calcium handling, torsades de pointes ventricular arrhythmias, and sudden cardiac death. 39 , 40 Of further direct relevance is a recent study showing that empagliflozin ameliorates dysfunctional sodium and calcium homeostasis in cardiomyocytes from diabetic rat hearts in part via inhibition of late- I Na .…”
mentioning
confidence: 99%
“…The small, sustained sodium current, I Na,late (Antzelevitch et al, 2014; Horvath and Bers, 2014), is also expressed heterogeneously in the ventricle wall of some species. This current, although much smaller than the peak I Na (less than 0.1%,(Antzelevitch et al, 2014)), can have significant effects on the cardiac action potential and plays an important role in many pathologies such as arrhythmias and heart failure (Antzelevitch et al, 2014; Horvath and Bers, 2014).…”
Section: Transmural Gradient In Ina Densitymentioning
confidence: 99%
“…This current, although much smaller than the peak I Na (less than 0.1%,(Antzelevitch et al, 2014)), can have significant effects on the cardiac action potential and plays an important role in many pathologies such as arrhythmias and heart failure (Antzelevitch et al, 2014; Horvath and Bers, 2014). INa, late has been shown to contribute to transmural electrical heterogeneity in the canine ventricle, with larger current densities observed in the mid-myocardium compared to the epicardium and endocardium (Zygmunt et al, 2001).…”
Section: Transmural Gradient In Ina Densitymentioning
confidence: 99%